What is wrong with Fanconi anemia cells? - Cantor, Sharon B (Cell Cycle, 2014)
Figuring out what is wrong in Fanconi anemia (FA) patient cells is critical to understanding the contributions of the FA pathway to DNA repair and tumor suppression. Although FA patients exhibit a wide range of disease manifestation as well as severity (asymptomatic to congenital abnormalities, bone marrow failure, and cancer), cells from FA patients share underlying defects in their ability to process DNA lesions that interfere with DNA replication. In particular, FA cells are very sensitive to agents that induce DNA interstrand crosslinks (ICLs). The cause of this pronounced ICL sensitivity is not fully understood, but has been linked to the aberrant activation of DNA damage repair proteins, checkpoints and pathways. Thus, regulation of these responses through coordination of repair processing at stalled replication forks is an essential function of the FA pathway. Here, we briefly summarize some of the aberrant DNA damage responses contributing to defects in FA cells, and detail the newly-identified relationship between FA and the mismatch repair protein, MSH2. Understanding the contribution of MSH2 and/or other proteins to the replication problem in FA cells will be key to assessing therapeutic options to improve the health of FA patients. Moreover, loss of these factors, if linked to improved replication, could be a key event in the progression of FA cells to cancer cells. Likewise, loss of these factors could synergize to enhance tumorigenesis or confer chemoresistance in tumors defective in FA-BRCA pathway proteins and provide a basis for biomarkers for disease progression and response.